Hydroxyapatite-TiO2 composites - OKTAR, FAİK NÜZHET (ELSEVIER SCIENCE BV, 2006)
This article reports the mechanical properties, the microstructure, and the crystallography of composite materials made of hydroxyapatite, obtained from natural bovine bone, and TiO2 (5 and 10 wt.%), which were sintered at different temperatures between 1000 and 1300 degrees C. Higher sintering temperatures resulted in better densification. The samples sintered at 1300 degrees C had the highest microhardness. The best compressive strengths were obtained after sintering at 1300 degrees C for the samples containing 5% TiO2, and at 1200 degrees C for the samples with 10% TiO2. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: hydroxyapatite; titanium oxide; sintering; mechanical properties; MECHANICAL-PROPERTIES; TITANIUM; COATINGS